Training Evaluation of Field Veterinarians: Implications for Scaling Up - M. Ravi Kumar; K. Gabriel; P.V.K. Sasidhar (Journal of Agricultural Extension Management, 2017)
This paper presents the evaluation .findings on effectiveness of gynecological training programmes organized for field veterinarians in Andhra Pradesh. The key evaluation questions were on training methodology, relevance of course content, knowledge and skill improvement, utility of the topics and overall effectiveness of the programmes. The .findings indicated a high relevance of the contents with overall increase of 29. 03 per cent knowledge and skill gain by the participants. The .findings also suggested that field veterinarians' competencies have been improved using a combination of theoretical, practical and field exposure sessions in an organized way. It is recommended to standardize the curriculum and scale-up training programmes to all field veterinarians as open education resources to update their competencies